Switched-capacitor step-down DC-DC converter - Muhammad Ridhwan Malik (2015)
Conservatively, the buck converter has been a common orientation of switched-mode voltage regulators in the past decades. In addition to this, the introduction and application of Switched-Capacitor (SC) DC-DC converters were mainly for low-powered systems or devices where efficiency was not considered to be an essential priority. In recent times, the technological advancements in power electronics have seen the maturation of many configurations of traditional power electronic circuits. An example of such a circuit is the SC DC-DC converter. Continuous efforts have been made to improve the compactness, durability and efficiency of the circuit through the reduction of the components used as well as the improved specifications of these components. These converters usually consist of switches, capacitors or MOSFETs. The SC DC-DC converter presents itself as a form of quintessential power supply for applications such as mobile electronic systems. SC converters today are becoming one of the current high-efficiency converters with low EMI emissions and they possess the ability for Buck (Step-Down) or Boost (Step-Up) operations. An efficient SC converter is dependent on the correct switching frequency, capacitor values and width & length of the MOSFET switches. In this report, the 2 methods applied in designing the SC converter were SPICE MOSFET integration and Parametric Analysis for the width and length of the MOSFETs. SPICE MOSFET integration is the linking of industrial SPICE MOSFET model files to created block symbols in a circuit schematic design. The block symbols will adopt the technical specifications of these MOSFET models and circuit simulation can be performed based on these technical data values of the MOSFETs. Another method used was using parametric analysis to derive the width or length of the MOSFET based on a set design parameter, which in this case, was the drain current, ID, of the MOSFET. The manual derivation of an accurate width and length of the MOSFET can be a long process but it is a vital step in obtaining a high efficiency SC DC-DC converter. The efficiency of the converter was calculated based on the step-down performance of the converter. The converter designed had a efficiency of 1.372×10!!% and this showed that the SC converter did not function ideally. The low efficiency was due to the low output current of the converter. The entire design and calculation process would be explained later in the report. This report summarises and documents the progress and technical achievements/breakthrough obtained for this Final Year Project (FYP). The FYP is titled “Switched-Capacitor Step-Down DC-DC Converter,” and it is a yearlong academic module. The project requires intensive research, analysis, simulation, design development and testing. This report will also educate readers on the overall objective, nature of the project, the progress achieved during the course of completion, results & analysis, conclusions as well as the future plans for development.